Digital Human Resource Transformation: The Role of Strategic HRM Capability and Learning Agility in Building Organizational Resilience in the Manufacturing Industry - Muhammad Angga Abdulah; Muhamad Ekhsan; Anna Wulandari (International Journal of Management Science and Information Technology, 2026)
Digital transformation has reshaped how manufacturing firms organize work and manage employees. In this setting, resilience depends not only on technology, but also on the capacity of the HR function to align people, skills, and organizational priorities. This study investigates whether Strategic Human Resource Management (HRM) Capability strengthens Organizational Resilience directly and through Learning Agility. The research was conducted among employees of manufacturing companies operating in five industrial areas in West Java: KIIC, EJIP, GIIC, Jababeka Industrial Estate-Cikarang, and MM2100 Industrial Town. Using a quantitative explanatory design, data were collected through a survey of 75 permanent employees selected purposively. Eligible respondents had at least one year of work experience and were involved in work processes affected by digital transformation. The model was tested with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Strategic HRM Capability has a positive and significant relationship with both Organizational Resilience and Learning Agility. Learning Agility also contributes positively and significantly to Organizational Resilience. Nevertheless, its indirect role was not statistically significant, indicating that the influence of Strategic HRM Capability on resilience operates mainly through a direct pathway rather than through Learning Agility. These results suggest that manufacturing firms should place greater emphasis on strategic workforce alignment, digital HR practices, competency development, and adaptive work systems. Strengthening these capabilities can help organizations respond more effectively to technological disruption and uncertainty while maintaining continuity during digital transformation.